2010
DOI: 10.1111/j.1468-3083.2010.03637.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in psoriatic scalp hair follicles: clobetasol propionate shampoo 0.05% normalizes psoriasis disease markers

Abstract: Hair follicles of SP patients are affected by the inflammatory process. The change in the expression level of inflammation-related genes correlates with the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…[10][11][12] Noninvasive and minimally invasive means, including skin tape stripping, abrasion methods, reverse iontophoresis and hair root sampling, are therefore of increasing interest to access biochemical, molecular and genetic processes. [13][14][15][16] Recent publications report proteomic profiling of the stratum corneum (SC) in atopic dermatitis. [17][18][19] In psoriatic scales, although it has been known since pioneering work in the late 1970s that several chemokines are present, [20][21][22] only few studies report the parallel analysis of a number of chemokines and cytokines in psoriatic scales.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Noninvasive and minimally invasive means, including skin tape stripping, abrasion methods, reverse iontophoresis and hair root sampling, are therefore of increasing interest to access biochemical, molecular and genetic processes. [13][14][15][16] Recent publications report proteomic profiling of the stratum corneum (SC) in atopic dermatitis. [17][18][19] In psoriatic scales, although it has been known since pioneering work in the late 1970s that several chemokines are present, [20][21][22] only few studies report the parallel analysis of a number of chemokines and cytokines in psoriatic scales.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Biomarker measurements in psoriasis are typically based on protein‐ or mRNA‐level quantification using invasive skin biopsy procedures, which can be associated with scarring, pain, risk of infection and allergic reactions . Noninvasive and minimally invasive means, including skin tape stripping, abrasion methods, reverse iontophoresis and hair root sampling, are therefore of increasing interest to access biochemical, molecular and genetic processes …”
mentioning
confidence: 99%
“…Clobetasol propionate (CP), a potent glucocorticoid, has been used in many different clinical trials and was shown to be effective for various inflammatory-caused scalp diseases, e.g. AA, LPP, FFA, and scalp psoriasis [4][5][6][7][8][9]. However, the described therapies are tedious for the patient as they entail application of an ointment to the desired site of action under occlusion with a plastic film, or application of a shampoo, cream, or foam several times a day for efficient treatment, all of which resulting in decreased patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…The expressionof IL8 gene was induced by the irritants in bulge-derived keratinocytes (BDKs) 44 . IL8 expression was significantly increased in psoriatic hair follicles 45 . Altogether, these results suggest that IL8 might be involved in wool growth regulation.…”
Section: Analysis Of Highly Differentially Expressed Genes (>10-fold)mentioning
confidence: 92%